Active on many foreign markets: A portrait of German multi-market exporters and importers from manufacturing industries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2017)
This paper uses information on more than 160 million export and import transactions by German firms from 2009 to 2012 to document the decisive role of multi-market traders that are active on many foreign markets, where a market is defined as a combination of a good traded and a country traded with. Using merged information from trade transactions and from surveys conducted by the statistical offices it is shown that, controlling for detailed industry affiliation, the number of foreign markets a firm from manufacturing industries is active on as an exporter or importer is higher in firms that are larger, older and foreign owned and that have higher labor productivity, human capital intensity and R&D intensity. With the exception of labor productivity these results are valid ceteris paribus, too. All these empirical results are in line with hypotheses that are derived from the literature on the links between firm characteristics and the extensive margins of foreign trade.
Keywords: F14; 330; Exports; Imports; Transaction level data; Germany